The initial psychotherapy interview : a gay man seeks treatment - Silverstein, Charles (Elsevier insights., 2011)
This book provides comprehensive coverage of the initial interview with a gay male client. It first provides a transcript of the entire interview. It then covers in depth a set of universal themes, and finally includes commentary on, and analysis of the interview from a range of the most widely used theoretical perspectives. It is designed to teach the foundations of conducting an initial interview and therapists in training, as well as experienced mental health workers will find it invaluable.